2019
DOI: 10.1177/0143831x19880265
|View full text |Cite
|
Sign up to set email alerts
|

Good intentions meet harsh realities: Social dialogue and precarious work in industrial cleaning

Abstract: This article offers a comparative study of recent joint initiatives by Danish and German social partners within the industrial cleaning sector. It examines how, and to what extent, the day-to-day realities of industrial cleaners vary due to distinct regulatory regimes and explores why social dialogue initiatives have not had a greater impact in terms of improving wages, working conditions and social benefits. The authors find that, whilst sector institutions help counteract precariousness for some cleaning wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…As Kelman (2002, p. 12) stated, 'the system continues to exist more to avoid corruption than to generate incremental value creation'. As a result of a lack of a 'whole-of-government' perspective, the cost of addressing the negative social and environmental externalities of low-bid public procurement continues to be downloaded to taxpayers, causing expenditures to rise in other departments of government (Erridge, 2007;Jaehrling, 2015;Jaehrling et al, 2018;Larsen et al, 2019;Lloyd and McCue, 2004;Schulten et al, 2012;Šličiuvienė, 2017;Sturgess, 2017;Telles, 2017). Telgen et al (2007) found that the delivery of broader government objectives, such as SDG 12.7 sustainable public procurement, is only possible at the most advanced levels of public procurement maturity.…”
Section: The Un Sdgs and Public Procurement In The Twenty-first Centurymentioning
confidence: 99%
“…As Kelman (2002, p. 12) stated, 'the system continues to exist more to avoid corruption than to generate incremental value creation'. As a result of a lack of a 'whole-of-government' perspective, the cost of addressing the negative social and environmental externalities of low-bid public procurement continues to be downloaded to taxpayers, causing expenditures to rise in other departments of government (Erridge, 2007;Jaehrling, 2015;Jaehrling et al, 2018;Larsen et al, 2019;Lloyd and McCue, 2004;Schulten et al, 2012;Šličiuvienė, 2017;Sturgess, 2017;Telles, 2017). Telgen et al (2007) found that the delivery of broader government objectives, such as SDG 12.7 sustainable public procurement, is only possible at the most advanced levels of public procurement maturity.…”
Section: The Un Sdgs and Public Procurement In The Twenty-first Centurymentioning
confidence: 99%
“…In terms of its main characteristics, the service is performed at the client's premises; the allocated workforce has an employment contract associated with a workplace and not with an enterprise (Bondy 2018;Eurofund 2014). The workplace may be occasional, in which workers belong to different service teams, or it may be habitual, resulting in a fixed workplace at the customer's premises (Larsen et al 2019). The complexity of the cleaning service provided varies, ranging from domestic households to hospital surgical blocks (EFCI-European Cleaning and Facility Services Industry 2020; Marconato et al 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, there is no professional recognition of this sector's workers or their tasks' importance (Brugière 2017). The majority earn minimum wage, and the working hours are generally outside the company's business hours, which implies working at night and/or early morning, as well as maintaining services, even at minimal levels, on festive dates and holidays (Eurofund 2014;Larsen et al 2019).…”
Section: Literature Reviewmentioning
confidence: 99%